Pencegahan Gagal Transaksi Pembelian Dan Pembayaran Industrial Blockchain Cryptocurrency Secara P2P (Peer To Peer) Melalui Arbitrase Internasional - Gallan, M.Sayyid Putra; Sutrisno, Nandang (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
Abstract This study discusses how digital asset transactions based on blockchain through peer-to-peer (P2P) networks often fail. This is generally due to a lack of effective conflict resolution mechanisms, delays in confirmation, and a lack of transparency in the execution of digital contracts. In such situations, conflicts that arise are often difficult to resolve through the courts due to cross-border jurisdictional factors and the complexity of the technology involved. This study explores how effective international arbitration can be as an alternative in preventing and resolving disputes arising from blockchain-based crypto transactions, particularly by leveraging arbitration clauses in digital trade contracts. This study emphasizes the role of the Singapore International Arbitration Centre (SIAC) with its 2025 Digital Assets Arbitration Rules, as well as decentralized resolution approaches such as Kleros. The methodology used in this study is a normative legal approach, supported by case studies and analysis of international legal regulations such as the 1958 New York Convention and the UNCITRAL Model Law. This research demonstrates that incorporating arbitration clauses covering jurisdiction, emergency arbitrators, and interim measures can reduce the risk of disputes and expedite the recovery process. International arbitration has proven capable of adapting to the characteristics of digital transactions, thereby potentially becoming the primary forum for dispute resolution within the digital asset-based financial ecosystem.